2013
DOI: 10.1371/currents.dis.c9c4f4db9887633409182d2864b20c31
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of Themes and Research Questions for Health Outcomes in Natural Disasters, Humanitarian Crises or Other Major Healthcare Emergencies

Abstract: People making decisions about interventions, actions and strategies for natural disasters, humanitarian crises and other major healthcare emergencies need access to reliable evidence to help ensure that the choices they make are likely to do more good than harm. However, there are many gaps in this evidence base in a wide range of areas. This paper reports a priority setting exercise that was coordinated by Evidence Aid to identify thirty priorities for up-to-date systematic reviews of the effects of intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…As a consequence, Evidence Aid has worked with a wide variety of people and organizations from the disaster and humanitarian sectors in 2013 to create a list of top priority questions in need of research and systematic reviews. 8 Although it was recognized that Evidence Aid would not be able to tackle all the research questions identified in this process, it would provide a means to gather them together for sharing with relevant agencies. The need to develop good communication, secure funding, and define and identify the relevant evidence featured highly in the final discussions and were accepted as important themes for the Third Evidence Aid Conference.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, Evidence Aid has worked with a wide variety of people and organizations from the disaster and humanitarian sectors in 2013 to create a list of top priority questions in need of research and systematic reviews. 8 Although it was recognized that Evidence Aid would not be able to tackle all the research questions identified in this process, it would provide a means to gather them together for sharing with relevant agencies. The need to develop good communication, secure funding, and define and identify the relevant evidence featured highly in the final discussions and were accepted as important themes for the Third Evidence Aid Conference.…”
Section: Discussionmentioning
confidence: 99%